PERAN STAKEHOLDER DALAM PROGRAM PEMBERDAYAAN ANAK DISABILITAS DREAMWORK - Wulandari , Arinda Putri; Humaedi, Sahadi; Tri Raharjo, Santoso (Social Welfare Study Program, 2025)
Abstract. The Dreamwork program is a CSR program of PT Pertamina Patra Niaga Fuel Terminal Bandung which aims to empower the community, especially for children with disabilities. The success of corporate social responsibility (CSR) programs requires the involvement of various stakeholders to achieve optimal and sustainable goals. The purpose of writing this article is to discuss the role of stakeholders in the Dreamwork Program initiated by PT Pertamina Patra Niaga Fuel Terminal Bandung as part of the company's CSR in empowering children with disabilities. This study uses a descriptive qualitative approach with in-depth interview methods, observations, and documentation studies to analyze the involvement of various stakeholders in this program. The results show that the involvement of stakeholders, such as academics, government, civil society organizations, the private sector, and the media plays a significant role in supporting the sustainability of the program. Cross-sector collaboration with a pentahelix approach has proven effective in ensuring that the Dreamwork Program can have a broader social and economic impact on children with disabilities and their families. Keyword: Stakeholder engagement; empowerment of children with disabilities; corporate social responsibility; pentahelix collaboration; program dreamwork. Abstrak. Program Dreamwork merupakan program CSR PT Pertamina Patra Niaga Fuel Terminal Bandung yang bertujuan dalam rangka pemberdayaan masyarakat khususnya untuk anak disabilitas. Keberhasilan program tanggung jawab sosial perusahaan (CSR) memerlukan keterlibatan berbagai pemangku kepentingan untuk mencapai tujuan yang optimal dan berkelanjutan. Tujuan penulisan artikel ini untuk membahas peran stakeholders dalam Program Dreamwork yang diinisiasi oleh PT Pertamina Patra Niaga Fuel Terminal Bandung sebagai bagian dari CSR perusahaan dalam memberdayakan anak disabilitas. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode wawancara mendalam, observasi, serta studi dokumentasi untuk menganalisis keterlibatan berbagai pemangku kepentingan dalam program ini. Hasil penelitian menunjukkan bahwa keterlibatan stakeholders, seperti akademisi, pemerintah, organisasi masyarakat sipil, sektor swasta, dan media berperan signifikan dalam mendukung keberlanjutan program. Kolaborasi lintas sektor dengan pendekatan pentahelix terbukti efektif dalam memastikan bahwa Program Dreamwork dapat memberikan dampak sosial dan ekonomi yang lebih luas bagi anak disabilitas dan keluarganya. Kata Kunci: Stakeholder engagement; pemberdayaan anak disabilitas; corporate social responsibility; kolaborasi pentahelix; program dreamwork.